Angiogenesis involvement by octacalcium phosphate-gelatin composite-driven bone regeneration in rat calvaria critical-sized defect. (1st April 2019) - Kurobane, Tsuyoshi; Shiwaku, Yukari; Anada, Takahisa; Hamai, Ryo; Tsuchiya, Kaori; Baba, Kazuyoshi; Iikubo, Masahiro; Takahashi, Tetsu; Suzuki, Osamu
Graphical abstract: Abstract: Effect of octacalcium phosphate/gelatin composite (OCP/Gel) on angiogenesis was studied by its implantation in rat calvaria critical-sized defect in relation to bone regeneration for 2 and 4 weeks. The implantation of OCP/Gel disks was analyzed by radiomorphometry using a radiopaque material perfusion (Microfil®) method and histomorphometry by hematoxylin and eosin-staining before and after the decalcification. Effect of the OCP dose in the range up to 4 mg per well on the capillary-like tube formation by human umbilical vein endothelial cells (HUVECs) was also examined in a transwell cell culture. The results showed that the blood vessels formation by OCP/Gel group was significantly higher at 2 weeks than other groups but decreased at 4 weeks during the advancement of new bone formation. The capillary-like tube formation was highest in an OCP dose of 1 mg per well while other OCP doses above or below 1 mg did not show such a stimulatory effect. The results established both in vivo and in vitro confirmed that OCP has a positive effect on angiogenesis during bone regeneration in a suitable dose ranges, suggesting that the angiogenesis stimulated by OCP could be involved in the OCP/Gel-enhanced bone regeneration. Statement of significance: We have reported that octacalcium phosphate (OCP) materials display stimulatory capacities on the bone tissue-related cells. However, the effect of OCP on the angiogenesis and its relation to the OCP-enhanced bone regeneration is unknown. This study confirmed the capacity of OCP on angiogenesis before increasing the new bone mass after the implantation of a composite of OCP and gelatin (OCP/Gel). The blood vessels formation took place associated with the area beginning of the new bone formation, which finally decreased together with development of bone formation. Because OCP was ascertained stimulating the capillary-like tube formation in HUVEC culture with a certain OCP dose, the present study is the first report showing the capacity of OCP on angiogenesis during the OCP/Gel-enhanced bone regeneration.